Optimalisasi Pemanfaatan Daun Rumbia untuk Pemberdayaan Ekonomi di Desa Teungoh Kuta Batee Kecamatan Meurah Mulia - Hidayatullah, Khalish Nur; Zikrillah, Muhammad; Ramadhana, Khairul; Munira, Najimah; Khatimah, Husnul; Nasution, Cici Laditah; Rahmah, Lysa Ida; Wati, Sukma; Nurhaliza, Siti; Alvionita, Vivi (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2025)
Rumbia palm is a natural resource with ecological, economic, and cultural potential, particularly in Teungoh Kuta Batee Village, Meurah Mulia District. Although traditionally used as a roofing material, its utilization has not yet been developed into a productive economic activity. This community service program aims to optimize the use of rumbia leaves through technical training and business mentoring to enhance the community’s economic empowerment. The method employed is a collaborative participatory approach, consisting of initial observation, interviews, and focus group discussions (FGD), technical training, and participatory documentation and evaluation. The activity involved lecturers and 13 students as implementers, with village residents as active partners. Training was conducted directly at local homes, covering topics such as leaf selection techniques, processing, stitching, and assembling rumbia leaf roofing. The results indicate improved community skills in producing high-quality, marketable rumbia leaf roofing. On average, artisans were able to produce 20–25 sheets per week, with a selling price of Rp 10,000–Rp 12,000 per sheet, generating additional income of Rp 200,000–Rp 300,000 weekly. The program also strengthened social solidarity and preserved traditional craftsmanship. Discussion reveals that this initiative successfully integrates economic, social, and environmental aspects into a locally grounded empowerment model. The activity aligns with sustainable development principles and can be replicated in other regions with similar characteristics. Strengthening community capacity through the utilization of local natural resources is key to realizing a self-reliant and competitive village.